Potret Feminisme dalam Cerpen “Jangan Pulang Jika Kamu Perempuan” Karya Riyana Rizki Yuliatin - Pipit Aprilia Susanti; Sartika Samad (Peneliti.net, 2023)
This research was conducted with the aim of looking at the forms of injustice experienced by women based on marginalization, stereotypes, and violence experienced by the main character in the short story